Utilization of Plants in the Traditional Ceremony Panggih Pengantin in Jombang Regency as Herbarium - Anti Qurrota A'yuni; Mucharommah Sartika Ami (FKIP, Universitas Palangka Raya, 2021)
The development of learning media based on local wisdom was needed to provide knowledge to the younger generation about their local culture. Local wisdom contains various positive values including pedagogical values so that they can be integrated into learning media. One of local wisdom that was still maintained by the people in Jombang Regency was the traditional ceremony Panggih Pengantin. In this series of traditional ceremony, various types of plants were used which can be used as Kingdom Plantae learning material in biology subjects. The learning media developed in this study was a herbarium. The purpose of this study was to describe the feasibility of the herbarium based on expert validation. This research was a type of research and development (R&D) that used five stages, namely potentials and problems, data collection, product design, design validation, and design revision. The instruments used were interview guides, observation sheets, questionnaires for herbarium expert and learning media expert. The data obtained were analyzed descriptively. The herbarium developed received a score of 80 (quite feasible) from the herbarium expert and a score of 95 (very feasible) from the learning media expert. The herbarium required a little revision according to the validators’ suggestions, so it was suitable for use as a biology learning media.